La Corporate Visual Identity (CVI) permet-elle réellement de se différencier ? - Philippe Boistel (Communication)
This research analyzes how banking firms use their Corporate Visual Identity (CVI) to differentiate themselves from their competitors. After reviewing the literature on the concept of CVI, the author examines the commercial practices of French banks and their positioning. He conducts two qualitative studies to determine the banks’ public images and how their CVIs are perceived. By comparing the results, he concludes that CVI is not a differentiating factor.